2018
DOI: 10.3389/fphys.2018.01711
|View full text |Cite
|
Sign up to set email alerts
|

A 2-Week Specific Volleyball Training Supported by the Whole Body Cryostimulation Protocol Induced an Increase of Growth Factors and Counteracted Deterioration of Physical Performance

Abstract: Potentially beneficial effects of cold therapies on training adaptation still remain unequivocal. We have, thus, decided to evaluate the effects of a 2-week volleyball training program supported by 10 sessions of whole body cryostimulation (WBC) on growth factors and physical performance. Twenty healthy college-aged men and women randomly assigned either to the cryostimulation group (CRY) or the control group (CON; executed passive rest). Both groups took part in the same 2-weeks training program. Additionally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 40 publications
1
21
0
Order By: Relevance
“…A recently published paper indicated that a 3 h exposure to 7 °C temperature did not affect myostatin gene expression [ 42 ]. In a separate study, the aforementioned protocol of whole-body cryostimulation, combined with specific volleyball training, had no impact on myostatin concentration [ 20 ]. Therefore, we concluded that the specific response to resistance training and cold treatment depended on the presence of a specific exercise stimulus.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A recently published paper indicated that a 3 h exposure to 7 °C temperature did not affect myostatin gene expression [ 42 ]. In a separate study, the aforementioned protocol of whole-body cryostimulation, combined with specific volleyball training, had no impact on myostatin concentration [ 20 ]. Therefore, we concluded that the specific response to resistance training and cold treatment depended on the presence of a specific exercise stimulus.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, this was only the effect of a single unit of exercise without any recovery-supporting method. In a previous investigation, a specific volleyball training program combined with cryostimulation did not significantly affect the concentration of IL-15 [ 20 ]. In our study, 12 units of regular resistance training with a workload comparable to the Perez-Lopez study, but combined with cryostimulation, caused a significant increase of IL-15 resting concentration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, different kinds of training models have been tested to improve the performance of volleyball players [14][15][16][17]. However, there is a high degree of inter-individual variation in the development of movement competence during early and middle childhood [18].…”
Section: Introductionmentioning
confidence: 99%